Adaptive and Participatory Financial Management in Private Vocational Schools: A Case Study of SMK Muhammadiyah 1 Taman Sidoarjo - Zuroida, Ida; Lasiyono, Untung; Afkar, Taudlikhul (Jurnal Manajemen Bisnis, 2025)
This study examines financial management strategies at SMK Muhammadiyah 1 Taman Sidoarjo, focusing on planning, implementation, and accountability in student programs. Using a qualitative case study, data were collected through observations, interviews, questionnaires, and document analysis. The results show that participatory budgeting through the annual work meeting increases transparency and stakeholder involvement, while adaptive strategies address budget discrepancies, such as graduation costs. Systematic bookkeeping supports accountability, though reliance on manual systems remains a challenge. The study concludes that effective school financial management requires participatory decision-making, adaptive strategies, and digital innovation to strengthen efficiency and sustainability.